Assessment of the Effectiveness of a Short-term Hearing Aid Use in Patients with Different Degrees of Hearing Loss - POREMSKI, Tomasz; SZYMAŃSKI, Piotr; KOSTEK, Bożena (Archives of Acoustics, 2019)
The study presents evaluating the effectiveness of the hearing aid fitting process in the short-term use (7 days). The evaluation method consists of a survey based on the APHAB (Abbreviated Profile of Hearing Aid Benefit) questionnaire. Additional criteria such as a degree of hearing loss, number of hours and days of hearing aid use as well as the user’s experience were also taken into consideration. The outcomes of the benefit obtained from the hearing aid use in various listening environments for 109 hearing aid users are presented, including a degree of their hearing loss. The research study results show that it is possible to obtain relevant and reliable information helpful in assessing the effectiveness of the shortterm (7 days) hearing aid use. The overall percentage of subjects gaining a benefit when communicating in noise is the highest of all the analyzed and the lowest in the environment with reverberation. The statistical analysis performed confirms that in the listening environments in which conversation is held, a subjective indicator determined by averaging benefits for listening situations individually is statistically significant with respect to the degree of hearing loss. Statistically significant differences depending on the degree of hearing loss are also found separately for noisy as well as reverberant environments. However, it should be remembered that this study is limited to three types of hearing loss, i.e. mild, moderate and severe. The acceptance of unpleasant sounds gets the lowest rating. It has also been observed that in the initial period of hearing aid use, the perception of unpleasant sounds has a big influence on the evaluation of hearing improvement.